2013
DOI: 10.2172/1116746
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Study on Thermal and Mechanical Design of Printed Circuit Heat Exchanger

Abstract: The analytical methodologies for the thermal design, mechanical design, and cost estimation of printed circuit heat exchanger are presented in this study. Three flow arrangements for PCHE of parallel flow, countercurrent flow and crossflow are taken into account. For each flow arrangement, the analytical solution of temperature profile of heat exchanger is introduced. The size and cost of printed circuit heat exchangers for advanced small modular reactors are also presented using various coolants such as sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…An analytical solution for a PCHE channel pair, such as the one modelled in this thesis, was developed by the Idaho National Laboratory [34]. The solution developed was for a counterflow configuration.…”
Section: Model Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…An analytical solution for a PCHE channel pair, such as the one modelled in this thesis, was developed by the Idaho National Laboratory [34]. The solution developed was for a counterflow configuration.…”
Section: Model Validationmentioning
confidence: 99%
“…The derivation is based off an energy balance of fluid control volumes, accounting for the overall heat transfer resistance between the streams, as presented in figure 21. [34] The equations developed for fluids 1 and 2 are as follows [34]: The indices i1 and i2 can have values of +1 or -1 and modify the equation set depending on whether a counterflow or parallel flow configuration is being analysed [34]. A positive value indicates flow in the same direction as the x axis, and vice versa.…”
Section: Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical results showed that the transition is observed at Reynolds numbers of 2300 for the circular and 3100 semicircular channels, while the heat transfer and pressure drop characteristics were also investigated. Yoon et al [52] from Idaho National Laboratory (INL) presented general methods for thermal design and cost estimation in order to determine the size, the thermalhydraulic characteristics and the cost of a crossflow PCHE. The effectiveness calculated by the developed code showed a good agreement with the results obtained with the ε-NTU method.…”
Section: Printed-circuit Heat Exchangersmentioning
confidence: 99%